Making Sense of Gov 2.0 Strategies: “No Citizens, No Party” - Enrico Ferro; Francesco Molinari (JeDEM - eJournal of eDemocracy & Open Government, 2010)
One of the main factors contributing to the limited impact of eParticipation projects is the presence of a high level of social complexity that has been identified by Macintosh as one of the five challenges in the implementation of eParticipation practices. How to make sense of social complexity is still an open issue as well as the way governments can take benefit from the wealth of information that is already available on their constituencies’ collective behaviour. In this paper, we contend that the presence of a considerable variance in terms of political interests, educational level and technological skills makes it very difficult to design workable and effective systems to support participation. A modular strategy is then recommended requiring policy designers to make a step towards citizens rather than expecting the citizenry to move their content production activity onto the “official” spaces created for ad hoc participation.